Pengaruh Video Animasi terhadap Kemampuan Mengenal Anggota Tubuh pada Anak - Yenti Juniarti; Yakob Napu; Della Safira Ointu (STKIP Muhammadiyah Kuningan, 2023)
Learning about body recognition is still minimal, children still do not understand which body parts can be touched and which others cannot touch. The aim of the study was to find out how animated videos affect the ability to recognize body parts in children aged 5–6 years at Beringin Kindergarten. The research method is quantitative, using video animation experiments and pre- and post-test research designs, the research subjects are 20 children aged 5–6 years, data collection techniques are observation, documentation. The results showed that there was an effect on the recognition of limbs before and after using video animation media, as evidenced by the total value obtained by the pretest, which was 11.7, after 8 treatments, there was an increase and change of 27.55; and the posttest obtained a value of 30.6. This proves a significant difference before and after giving treatment through animated video media for the introduction of body parts to children. The conclusion is that the recognition of body parts through the use of animated video media has an effect on the ability to recognize body parts